Changes in the preparedness of athletes engaged in track and field sprint in the conditions of a specialized sports club - Vjаcheslav Shutieiev (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to find out the influence on the preparedness of athletes-sprinters of the conditions for organizing training sessions in specialized sports clubs. Material & Methods: in the study, students (young men) of the first year (age 17), who wanted to practice athletic sprint in a specialized sports club, participated in only 18 people, of which two groups (control and experimental) were formed. To assess the level of preparedness of athletes used common types of testing. Results: conducted studies have shown that over the period of the experiment, the improvement in the results in the experimental group compared with the control group on average for all types of tests is 4,3%. Conclusion: results of the experiment show that the level of general physical preparedness (improvement is 2,4%), the special strength preparedness (an improvement of 6,3%) and the special cross-country preparedness (in comparison with the control group) 4,2%).